Recent progress in the preparation and application of quantum dots/graphene composite materials. Issue 76 (12th October 2017) - Tong, Ling; Qiu, Feng; Zeng, Tianjian; Long, Jia; Yang, Jie; Wang, Rongfei; Zhang, Jin; Wang, Chong; Sun, Tao; Yang, Yu
Abstract : Quantum dots/graphene (QDs/GR) composite materials show a distinct synergistic effect between the QDs and graphene, which has aroused vast attention toward their unique characteristics in the last few decades. Abstract : Quantum dots/graphene (QDs/GR) composite materials show a distinct synergistic effect between the QDs and graphene, which has aroused vast attention toward their unique characteristics in the last few decades. The separation of electron–hole pairs generated in QDs are enhanced due to the photogating effects in the composites, and then the electrons or holes are rapidly transferred to the surface of the graphene sheets, resulting in excellent optical gain, making them promising materials for applications in optoelectronic and light harvesting devices. In this review, recent research progress on QDs/GR composites is reviewed and discussed, including preparation methods and applications. Numerous self-assembly synthetic methods such as hydrothermal, solvothermal, atomic layer deposition, ion beam sputtering deposition, and other typical synthetic methods like drop-casting, spin-coating, layer by layer, ultrasonication, polymethylmethacrylate (PMMA) aid transfer and electrochemical methods are summarized and discussed. In addition, the applications of QDs/GR composites such as in photodetectors, lithium ion batteries, solar cells, photocatalysis, electrochemiluminescence (ECL) sensors and supercapacitors are described in detail. Finally, the prospects of QDs/GR composites are discussed.